NILAI-NILAI ISLAM DALAM KEARIFAN LOKAL KEHIDUPAN PERNIKAHAN DI DESA WINTAOS - Retno Firdiyanti; Nuril Bariroh (Universitas Islam Bandung, 2019)
Wintaos Girimulyo Village, Panggang Gunung Kidul, has local wisdom values that are typical in various aspects of their lives. But now the villagers of Wintaos have to fight against the globalization of the demands of the times that make them have to change their lifestyle more in line with the needs that are increasingly increasing. The values of local wisdom that they used to begin to shift along with the changing patterns of their lives which increasingly get the demands of necessity. Through this research, researchers want to investigate the values of the local wisdom of the Wintaos village community, especially in the aspect of marriage life. The method of collecting data is through the dept interview with two community leaders in the village of Wintaos. The research method uses qualitative methods with an explanatory approach to reveal the values of local wisdom in the community. Furthermore, the discovery of the values of local wisdom is analyzed and generalized into wise attitudes and soft skills as an alternative to living a married life. The results showed that the values of the local wisdom of Wintaos village could be soft skills education as an alternative way of living a prosperous marriage life